The Evaluation of the Solvent Fractions of the Fruits, Leaves, and the Stem Bark of Sarcocephalus latifolius (SM.) E. A. Bruce for Cytotoxicity and Antioxidant Activities - Imah-Harry, J. U.; Omotosho, S. O.; Odine, G. O. (Journal of Science, Technology and Innovation Research, 2026)
The geared trend in using medicinal plants in the management of various human ailments, cancer inclusive has gained significant consideration. Despite the innovations in technology, and the advent of foremost therapies, there is a growing inclination towards herbal medicine. In traditional medicine, Sarcocephalus latifolius (SL) is utilized to treat cancer; however, its efficacy in doing so has not been scientifically confirmed or supported by empirical data. The study evaluated the antioxidant and the cytotoxicity profile of the fruits, leaves and the stem bark of SL. These plant parts were harvested, washed, air-dried, pulverised and soaked in 100% methanol to obtain the crude methanol extracts (CMESL, MCESLL and CMESBSL). These were partitioned successively between n-hexane chloroform, ethyl acetate and methanol to obtain their respective fractions, N-hexane (HFSL, HFSLL and HFSBSL), chloroform (CFSL, CFSLL, and CFSBSL), ethyl acetate (EFSL, EFSLL, and EFSBSL), and the methanol (MFSL, MFSLL and MFSBSL). These extracts and fractions were subjected to in vitro antioxidant assays (DPPH, TAC, TPC and FRAP) and an in vivo cytotoxicity test using the brine shrimp lethality test (BSLT), to determine their LC50. The results reveal that CFSL, CFSLL and CFSBSL is the most cytotoxic when compared to the other fractions, and for the antioxidant assays, the ethyl acetate fractions of the leaves and stem bark, EFSLL, and EFSBSL and the chloroform fraction, CFSL of the fruits, had the peak activity. Sarcocephalus latifolius plant demonstrates the potential as a rich reservoir for antioxidants and might have bioactive agents responsible for the anticancer effects.